“What Women Like”: Influence of Motion and Form on Esthetic Body Perception - Cazzato, Valentina; Siega, Serena; Urgesi, Cosimo (Frontiers in Psychology, 2012)
Several studies have shown the distinct contribution of motion and form to the esthetic evaluation of female bodies. Here, we investigated how variations of implied motion and body size interact in the esthetic evaluation of female and male bodies in a sample of young healthy women. Participants provided attractiveness, beauty, and liking ratings for the shape and posture of virtual renderings of human bodies with variable body size and implied motion. The esthetic judgments for both shape and posture of human models were influenced by body size and implied motion, with a preference for thinner and more dynamic stimuli. Implied motion, however, attenuated the impact of extreme body size on the esthetic evaluation of body postures, and body size variations did not affect the preference for more dynamic stimuli. Results show that body form and action cues interact in esthetic perception, but the final esthetic appreciation of human bodies is predicted by a mixture of perceptual and affective evaluative components.